A Porous π-Stacked Self-Assembly of Cup-Shaped Palladium Complex for Iodine Capture - Lin-Lin Li; Min Huang; Ting Chen; Xiao-Feng Xu; Zhu Zhuo; Wei Wang; You-Gui Huang (Molecules, 2023)
Acquiring adsorbents capable of effective radioiodine capture is important for nuclear waste treatment; however, it remains a challenge to develop porous materials with high and reversible iodine capture. Herein, we report a porous self-assembly constructed by a cup-shaped PdII complex through intermolecular π···π interactions. This self-assembly features a cubic structure with channels along all three Cartesian coordinates, which enables it to efficiently capture iodine with an adsorption capacity of 0.60 g g−1 for dissolved iodine and 1.81 g g−1 for iodine vapor. Furthermore, the iodine adsorbed within the channels can be readily released upon immersing the bound solid in CH2Cl2, which allows the recycling of the adsorbent. This work develops a new porous molecular material promising for practical iodine adsorption.